2015
DOI: 10.1002/jnr.23614
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically relevant factors influence tau phosphorylation by leucine‐rich repeat kinase 2

Abstract: Hyper-phosphorylation and aggregation of tau are observed in multiple neurodegenerative diseases, termed tauopathies. Tau has also been implicated in the pathogenesis of Parkinson’s disease (PD) and parkinsonisms. Interestingly, a subset of PD patients with mutations in the Leucine-rich repeat kinase 2 (LRRK2) gene exhibit tau pathology. Mutations in LRRK2 are a major risk factor for PD, but LRRK2 protein function remains unclear. The most common mutation, G2019S, is located in the kinase domain of LRRK2 and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Phosphorylation is thought to increase tau's neurotoxicity [70] but the influence of phosphorylation on ␣-synuclein's toxicity is unclear [71]. Although some studies have suggested that LRRK2 may phosphorylate ␣synuclein [72] and/or tau [73][74][75], the only presently accepted bona fide LRRK2 kinase substrates are LRRK2 protein itself and some Rab GTPases [76,77] such as Rab10, as mentioned above.…”
Section: Pd-associated Lrrk2 Gene Mutationsmentioning
confidence: 99%
“…Phosphorylation is thought to increase tau's neurotoxicity [70] but the influence of phosphorylation on ␣-synuclein's toxicity is unclear [71]. Although some studies have suggested that LRRK2 may phosphorylate ␣synuclein [72] and/or tau [73][74][75], the only presently accepted bona fide LRRK2 kinase substrates are LRRK2 protein itself and some Rab GTPases [76,77] such as Rab10, as mentioned above.…”
Section: Pd-associated Lrrk2 Gene Mutationsmentioning
confidence: 99%
“…As mentioned above, a number of reports have described that LRRK2 promotes tau phosphorylation in the brain in BAC-based transgenic mice as well as in knock-in mice of FPD mutant forms of LRRK2. Whereas the direct phosphorylation of tau by recombinant LRRK2 in an in vitro assay has been observed [166], some reports suggested that LRRK2 phosphorylates tau in the presence of tubulin or microtubules [167,168]. Other reports proposed that LRRK2 directly interacts with GSK-3β via the LRRK2 kinase domain, and this interaction enhances the kinase activity of GSK-3β [169].…”
Section: Abnormal Tau Accumulationmentioning
confidence: 99%
“…The elongation, cargo recognition and completion steps could be affected by alterations in the levels of the clathrin adaptor protein PICALM, as reported in AD (Moreau et al, 2014); hyperphosphorylated Tau-dependent microtubules destabilisation, as in AD and PD (Hamm et al, 2015); defective cargo recognition/interaction, as reported for mHtt in HD, or TDP-43, SOD1 and FUS, in ALS (Menzies et al, 2017).…”
Section: Macro-and Selective-autophagy In Neurodegenerative Diseasesmentioning
confidence: 83%